2017
DOI: 10.1016/j.ajo.2017.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Macula Vessel Density Loss in Primary Open-Angle Glaucoma: A Longitudinal Study

Abstract: Purpose To characterize the rate of macula vessel density loss in primary open angle glaucoma (POAG), glaucoma suspect, and healthy eyes. Design Longitudinal, observational cohort from the Diagnostic Innovations in Glaucoma Study. Methods One hundred eyes (32 POAG, 30 glaucoma suspect and 38 healthy) followed for at least one year with optical coherence tomography angiography (OCT-A) imaging on at least two visits were included. Vessel density was calculated in the macula superficial layer. The rate of cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
139
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(159 citation statements)
references
References 43 publications
11
139
1
2
Order By: Relevance
“…In the macular area the results were less clear than in the peripapillary area. One study found a significantly lower vessel density in PrG eyes in comparison to normal eyes [63]; a second study found a significantly lower vessel density in the inferior sector [47]; and a third study found a significantly greater vessel density in GS in comparison with control eyes [69]. In the latter, this might be explained by the fact that the GS group was significantly younger than the control group [69].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the macular area the results were less clear than in the peripapillary area. One study found a significantly lower vessel density in PrG eyes in comparison to normal eyes [63]; a second study found a significantly lower vessel density in the inferior sector [47]; and a third study found a significantly greater vessel density in GS in comparison with control eyes [69]. In the latter, this might be explained by the fact that the GS group was significantly younger than the control group [69].…”
Section: Resultsmentioning
confidence: 99%
“…Because OCTA is a recently developed technique, only limited research has been published about its ability to detect progression [63, 84]. …”
Section: Resultsmentioning
confidence: 99%
“…In this study, we set the cutoff value of OCTA image quality at SSI >48, as used in many previous studies. 23,25,26,36,[39][40][41][42] Venugopal et al recently reported that SSI value had a significant effect on the repeatability of VD measurement by OCTA. 43 The mean SSI values of our cohort were relatively high, being close to 60, and there was no significant difference among groups in terms of SSI values.…”
Section: Discussionmentioning
confidence: 99%
“…34,35,37,38 Thus, AL-related magnification factor can be corrected by Dt ¼ 3.460*0.01306*(AL À 1.82)*Dm. 34,35,37,38 Poor quality OCTA images were excluded from the analysis, including signal strength index (SSI) < 48 (minimum ¼ 1, maximum ¼ 100) 23,25,26,36,[39][40][41][42] ; poor-clarity images due to severe media opacities; motion artifacts or localized weak signal by vitreous floaters; residual motion artifacts visible as irregular vessel patterns or disc boundary on the en face angiogram; images not centered on the fovea for macular OCTA (fixation error); and segmentation failure.…”
Section: Octa Image Acquisition and Processingmentioning
confidence: 99%
See 1 more Smart Citation